7. MOLECULAR IDENTIFICATION AND PHYLOGENETIC RELATIONSHIP OF DEMODEX MITES IN THE DEMODICOSIS’ PATIENTS BASED ON MITOCHONDRIAL 16S rDNA TECHNIQUE (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine of Demodex species and phylogenetic relationship by molecular techniques.Methods: DNA were isolated from the demodicois patients’ Demodex mites and used for PCR amplification of mitochondrial (mt) 16S rDNA. The amplified PCR product were purified and used for molecular identification. The amplified mt16s rDNA product was sequenced and characterized to BLAST search in the NCBI database for molecular identification.Results: All of 12 identified Demodex samples belongs to Demodex folliculorum. The phylogenetic tree constructed by using mt16s rDNA sequence suggests that D. folliculorum is closer to D. brevis. All the isolates belong to D. folliculorum and the mitochondrial DNA 16S rDNA partial sequence is applicable for phylogenetic relationship analysis, but not for interspecies identification.Conclusions: All of 12 isolates belong to D. folliculorum, and the mitochondrial 16S rDNA partial sequence is applicable for phylogenetic relationship analysis at the genus-species level.
Keywords: Demodex spp; Demodex folliculorum; mt 16S rDNA; phylogenetic relationship